VALIDASI BEHAVIORAL ACTIVATION DALAM MENINGKATKAN MANAJEMEN DIRI PADA PASIEN ASMA - , MEGA DIANINGTYAS NUGRAHENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Psychological treatment as an alternative model of treatment in patients with asthma that could improve their self-management, that affected the quality of life. Self-management in asthma patients could be seen in the change of behavior to maintain physical condition and health. Behavioral Activation (BA) was one of the techniques with behavioral approaches that focus on improving behavior. The purpose of this study was to validate the module treatment Behavioral Activation in improving self-management of patient with asthma in Puskesmas. This study used a quasi-experimental design with untreated control group design with pretest and posttest. Research subjects were individuals, who were diagnosed with asthma and had poor self-management, divided into experimental group (n=4) and control group (n=4). Behavioral checklist for self-management and the Beck Depression Inventory (BDI) were measuring instrument that be used. Data analysis used the Anova. The results indicated that the BA module valid in improving selfmanagement in patient with asthma in Puskesmas, but self-management of patient with asthma has not been increased optimal. Keyword: Behavioral Activation, self-management, asthma, quasi experimental